Efficiency of prebiotics and probiotics on the performance, yield, meat quality and presence of Salmonella spp in carcasses of free-range broiler chickens - Takahashi, S E [UNESP]; Mendes, Ariel Antonio [UNESP]; Saldanha, E S P B; Pizzolante, C C; Pelícia, K [UNESP]; Quinteiro, R R [UNESP]; Komiyama, C M [UNESP]; Garcia, R G [UNESP]; Paz, Ibiara Correia de Lima Almeida [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2005)
Two trials were carried out in the present study. Trial I evaluated the performance, carcass yield and breast meat quality, whereas Trial II evaluated the efficacy of utilizing prebiotics + probiotics on the control of Salmonella spp incidence in the carcasses of free-range broilers. In Trial I, 688 one-day-old male chicks of the Naked Neck Label Rouge strain were used, distributed in a randomized block design arranged according to a 2 x 2 factorial: control diet or diet supplemented with probiotics and prebiotics; and two rearing systems (confined or with access to paddocks - 3m²/bird), using four replicates with 35 birds each. The birds were reared until 84 days of age following the recommendations of management and nutrition for free-range strains, and had access to paddocks after 35 days of age. Water and food were given inside the experimental poultry house. Birds fed probiotics and prebiotics in the diet and the confined birds showed better performance, carcass yield and meat quality compared to the birds of the other treatments. In Trial II, 128 one-day-old male chicks of the free-range Naked Neck Label Rouge strain were used. The birds were distributed into four treatments: NCC (non-challenged control), NCS (non-challenged supplemented), CC (challenged control) and CS (challenged supplemented). There were no significant effects of adding probiotics and prebiotics in the diet in regard to Salmonella enteritidis recovery from the carcasses.
Keywords: Carcass yield; free-range broilers; performance; prebiotics and probiotics; Salmonella spp